Management of Hospital Customer Complaint Using E-Complaint - Ajeng Fitri Setyani; Bagoes Widjanarko; Farid Agushybana (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2019)
Hospital customer complaints must be responded with good complaint management and assisted with e-complaint applications. As a hospital that has applied e-complaint applications for two years, there has never been an evaluation of complaint management using this e-complaint application at the hospital both in terms of the time of complaint completion and quality improvement of hospital services. This study aimed to analyze the implementation of an e-complaint system for managing customer complaint at one of the type-C private hospitals in Central Java using the HOT FIT approach. This study was qualitative research with an exploratory case study design through in-depth interviews using HOT FIT variables, such as Human, Organization, Technology, and Net Benefit. This study involves 8 main informants and 3 triangulation informants. This study showed that organizational aspects play an important role in encouraging people to the successful implementation of technology. Organizational problems can influence time to resolve complaints due to weak monitoring conducted by superiors who can also relate to the use of complaints data as input for quality improvement. Without the support of organizational commitment to run the technology-based system, the benefits of the system will not be obtained to support complaint management. It is recommended for hospitals to optimize organizational functions for the system and encourage staffs so that they achieve the benefits of the system for the organization's performance.